2008
DOI: 10.1007/s10862-008-9080-6
|View full text |Cite
|
Sign up to set email alerts
|

Low Attentional Control and the Development of Intrusive Memories Following a Laboratory Stressor

Abstract: This study tested whether low attentional control set people at risk for experiencing undesirable intrusions. Participants completed measures of attentional control and neuroticism and subsequently watched an emotional film fragment. In the four days following the presentation of the fragment, half of the participants (n=17) were asked to keep a diary for the registration of intrusive memories. The other half of the participants (n=16) only rated the number of intrusions retrospectively during the follow-up se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Verwoerd et al (2008) also found that lower ACS scores predicted increase in diary ratings of intrusive thoughts over four consecutive days after watching an emotional film fragment, supporting the predictive validity of the scale. Support has also been found with self-report questionnaires for the hypothesized interaction between attentional control and predisposing factors when predicting symptoms of psychopathology.…”
Section: Introductionmentioning
confidence: 54%
See 1 more Smart Citation
“…Verwoerd et al (2008) also found that lower ACS scores predicted increase in diary ratings of intrusive thoughts over four consecutive days after watching an emotional film fragment, supporting the predictive validity of the scale. Support has also been found with self-report questionnaires for the hypothesized interaction between attentional control and predisposing factors when predicting symptoms of psychopathology.…”
Section: Introductionmentioning
confidence: 54%
“…As would be expected, the total score of the ACS has moderate negative correlations with self-report measures of trait-anxiety (Derryberry & Reed, 2001, cited in Derryberry & Reed, 2002, neuroticism (Verwoerd et al, 2008) and depressive symptoms (Reinholdt-Dunne, Mogg, & Bradley, 2009). Verwoerd et al (2008) also found that lower ACS scores predicted increase in diary ratings of intrusive thoughts over four consecutive days after watching an emotional film fragment, supporting the predictive validity of the scale.…”
Section: Introductionmentioning
confidence: 57%
“…Clips from this movie induced intrusive memories in several studies (e.g. Schaich, Watkins, & Ehring, 2013;Verwoerd, De Jong, & Wessel, 2008). Furthermore, a variety of physiological measures (cortisol level, heart rate, and pupil dilation) confirmed successful stress induction for these particular four scenes (Henckens et al, 2009), and a longer version of the rape scene elicited a higher heart rate, more distress, and more intrusive memories than three other trauma films (Weidmann, Conradi, Gröger, Fehm, & Fydrich, 2009).…”
Section: Film Conditionmentioning
confidence: 64%
“…Whether our speculation is borne out when other verbally interfering task are used immediately post-trauma should be tested. The scope of possible such deleterious effects soon after trauma requires delineation, and a range of potentially verbally/ conceptually interfering post-trauma tasks should be considered (see also for example Butler, Wells, & Dewick, 1995;Nixon, Cain, Nehmy, & Seymour, 2009;Verwoerd, de Jong, & Wessel, 2008). In the meantime, the current data suggest that verbal/conceptual interference during trauma encoding far from being beneficially distracting may actually have an undesired proliferation effect on flashbacks.…”
Section: Discussionmentioning
confidence: 83%